Design of IMC-PID controller with fractional-order filter for steam distillation essential oil extraction process - Siti Nur Hasinah Binti Johari; Mohd Hezri Fazalul Rahiman; Najidah Hambali; Ramli Adnan; Mazidah Tajjudin (Institute of Advanced Engineering and Science, 2021)
Essential oils are one of the industry's major compounds, particularly in the pharmaceutical, perfume and food sectors. They were acquired using several methods such as steam distillation. In this method, heat from the steam will release the aromatic molecule at their specific boiling points. Thus, it is important to regulate the steam temperature at the correct level to get the perfect composition of the yield. Many studies have shown that essential oil is volatile and sensitive to excess heat. In order to maintain the desired steam temperature, this study proposed an internal model control (IMC) based PID with fractional-order filter as a controller for this system. IMC is a model-based control structure that can handle parameter variations and load disturbance very well. With the inverse model imposed in the loop, IMC can gain a perfect tracking control as well. The implementation of a fractional-order filter cascaded to the PID controller may enhance the system robustness to process gain with its iso-damping properties. This study was conducted by simulation using MATLAB R2018. The step response of the closed-loop system has been evaluated with varying filter parameters depending on the desired phase margin of the open-loop reference model.